2005
DOI: 10.1111/j.1600-9657.2005.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Level of information concerning dental injuries and their prevention in Swiss basketball – a survey among players and coaches

Abstract: Basketball carries a medium risk of dental injuries. Swiss data are not available in this respect. Using a standardized questionnaire 302 basketball players from 29 Swiss teams and their 29 coaches were interviewed. The questions focused on the frequency of dental accidents, their prevention and subsequent procedure. The participating 302 players came from three divisions: semi-professional players of National League A and B (102), amateurs of Regional League 2 and 3 (100) and young people of up to the age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
147
4
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(185 citation statements)
references
References 32 publications
22
147
4
12
Order By: Relevance
“…A utilização de protetores bucais pode evitar ou reduzir a severidade dos principais acidentes na cavidade oral relacionados à prática esportiva, conforme demonstrado na literatura 8 e, mesmo assim, esses dispositivos não são bem aceitos em diversos tipos de esporte de contato 27 , a despeito de não provocarem quaisquer efeitos negativos sobre a força e desempenho do atleta 5 . Existem três tipos de protetores bucais estabelecidos pela Academy for Sports Dentistry 12,28 : estoque (tipo I), termoplástico (tipo II) e o personalizado (tipo III).…”
Section: Objectiveunclassified
“…A utilização de protetores bucais pode evitar ou reduzir a severidade dos principais acidentes na cavidade oral relacionados à prática esportiva, conforme demonstrado na literatura 8 e, mesmo assim, esses dispositivos não são bem aceitos em diversos tipos de esporte de contato 27 , a despeito de não provocarem quaisquer efeitos negativos sobre a força e desempenho do atleta 5 . Existem três tipos de protetores bucais estabelecidos pela Academy for Sports Dentistry 12,28 : estoque (tipo I), termoplástico (tipo II) e o personalizado (tipo III).…”
Section: Objectiveunclassified
“…Injuries are very common in sports, especially in those modalities involving more speed and close contact between athletes, which are more susceptible to facial and dental trauma (15). The main causes of sports-related dental trauma are falls and collisions with people or objects.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in accordance with a study of Erhan and co-workers (16) who demonstrated that trauma type (Luxation) was significantly increased during a 1-year period of playing. The mandatory wear of mouthguards in various sports like American football, rugby and boxing, makes it possible the prevention of dental injuries (21). However, in soccer, mouthguard wear is not mandatory; consequently, the incidence of dental trauma is higher than other sports considered more violent, like martial arts (22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spor kaynaklı travmaların diğer travmalardan farkı ağız koruyucusu kullanarak bu yaralanmaları engellemek veya anlamlı ölçüde azaltılabilmektir. Spor kaynaklı dental travmalar hakkında yapılan çalışmalar incelendiğinde, travmalardan korunma yöntemleri ve travma sonrası acil müdahale açısından sporcuların farkındalık oranlarının düşük olduğu görülmüştür [51][52][53][54][55][56][57][58]. Sporcular, koçlar, antrenörler ve bu alanda çalışan bireyler dental travmalardan korunma ve travma esnasında yapılabilecek acil müdahaleler hakkında bilinçlendirilmeli ve daha kapsamlı eğitim almaları sağlanmalıdır.…”
Section: Tartişma Ve Sonuçunclassified